2021
DOI: 10.2217/fon-2021-0341
|View full text |Cite
|
Sign up to set email alerts
|

Navigating the High Costs of Cancer Care: Opportunities for Patient Engagement

Abstract: Over the past decade, the financial burden of cancer care on patients and their families has garnered increased attention. Many of the potential solutions have focused on system-level interventions such as adopting value-based payment models and negotiating drug prices; less consideration has been given to actions at the patient level to address cancer care costs. We argue that it is imperative to develop and support patient-level strategies that engage patients and consider their preferences, values and indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 91 publications
(99 reference statements)
0
2
0
Order By: Relevance
“…JL, like many under-insured patients, was inadvertently overlooked by her oncology team to be at risk for what scholars refer to as "financial toxicity, " or the material and psychosocial hardship from high costs of care. Yet, as many as 64% of patients report financial hardship following a cancer diagnosis [1], and many face barriers, like those described above, that prohibit affordable access to needed cancer therapies [2,3]. We use this case study to describe the critical steps we took to adapt and implement a health insurance decision intervention for cancer patients and survivors like JL, while balancing intervention testing and adaptation with real-world needs during a global pandemic.…”
Section: Open Accessmentioning
confidence: 99%
“…JL, like many under-insured patients, was inadvertently overlooked by her oncology team to be at risk for what scholars refer to as "financial toxicity, " or the material and psychosocial hardship from high costs of care. Yet, as many as 64% of patients report financial hardship following a cancer diagnosis [1], and many face barriers, like those described above, that prohibit affordable access to needed cancer therapies [2,3]. We use this case study to describe the critical steps we took to adapt and implement a health insurance decision intervention for cancer patients and survivors like JL, while balancing intervention testing and adaptation with real-world needs during a global pandemic.…”
Section: Open Accessmentioning
confidence: 99%
“…Cancer is a chronic disease that requires patients to engage with a health care team over time to discuss different treatment options [ 28 ]. PE in cancer care delivery results in higher quality of care, greater patient satisfaction, and improved cost containment [ 29 - 31 ]. Although further research is needed on the use of HIT among older adults diagnosed with cancer, it has been observed that these patients tend to demonstrate higher levels of activation and engagement in their health care.…”
Section: Introductionmentioning
confidence: 99%